Pompeii : Monuments Past and Present - De Franciscis, Alfonso and Bragantini, Irene; Consulting Editor Parton, James and Sponsored by the Air Force Historical Foundation (Roma Vision, 1995)
"This book explores Pompeii with an eye toward contrasting what it is today and how it appeared before this fabled city was buried beneath a rain of ash and cinders during the eruption of Vesuvius in 79 A.D. This tour includes the Porta Marina, one of the best preserved gates to the city, as well as the Forum, Temple of Apollo, and several public walkways and private villas. Important monuments and districts are presented with overlays that clearly depict how these notable ancient sites look today and how they likely appeared when they were first built, making these titles resources for travelers, students, and anyone interested in the fascinating history of Pompeii."--Jacket
Includes Colored Illustrations.
Keywords: Pompeii (Extinct city) -- Guidebooks